Implementação e avaliação de modelos computacionais para a previsão da erosão em ciclones - Martins, Diego Alves de Moro (2016)
Numerical simulations to predict erosion in cyclone separators due to the impact of particles were accomplished in this work. The predictions were performed through Computational Fluid Dynamics methods. The geometry investigated was similar to that of a second stage cyclone of a fluidized catalytic cracking unit. The numerical results were compared to experimental results available in the literature. The cyclone walls were made of acrylic with multiple coatings of drywall in the experiments. However, the implemented models to predict the erosion were developed for metallic materials. In this context, the validation was performed with cases in which the materials involved were the same as that used in the implemented models. The influence of the two-phase models, turbulence modelling, mesh resolution, dipleg presence and the models of particle/wall collision in erosion were evaluated after the validation. It was found that the turbulence modelling and mesh resolution were the most relevant factors in the erosion prediction, at least in the studied cases. Another relevant parameter is the friction factor, whose value significantly modifies the erosion rate. It was noticed that the interaction between the fluid and the particles reduces the erosion rate, even at low concentrations, as well as the interparticle collisions. Generally, the eroded regions were observed to match those from the experiments.